Determinants of Entrepreneurial Intentions Among Polytechnic Students: Evidence from Indonesia - Alek, Muhammad Rudi (Journal of Supply Chain and Entrepreneurship, 2025)
Aim: This study aims to examine the simultaneous influence of entrepreneurship education, family environment, and income expectations on the entrepreneurial intention of vocational college students in Indonesia. Method: A quantitative survey method was applied, involving 100 students from Politeknik Negeri Jember who had completed entrepreneurship courses. Data were collected through structured questionnaires and analyzed using classical assumption tests, multiple linear regression, and hypothesis testing, supported by validity and reliability assessments. Findings: The results indicate that family environment and income expectations significantly affect entrepreneurial intention, while entrepreneurship education has no significant impact. Among the variables, income expectations emerged as the most dominant factor. These findings highlight the strong influence of personal and familial contexts on students’ entrepreneurial aspirations, particularly within the vocational education setting. Significance: This research contributes to the understanding of entrepreneurial behavior among vocational students by identifying key motivational drivers. The findings offer practical implications for educational institutions and policymakers to redesign entrepreneurship programs that integrate real-world experiences, parental involvement, and income-related motivation to foster entrepreneurial potential in vocational learners.